Long-term prevention of hypertension and end-organ damage in Ren-2 transgenic rats is achieved only with persistent but not transient AT1 receptor blockade - Vaněčková, Ivana; Kopkan, Libor; Husková, Zuzana; Vaňourková, Zdeňka; Schejbalová, Stanislava; Červenka, Luděk; Kramer, Herbert J (Kidney & blood pressure research, 2007)
The aim of this study was first to evaluate the effects of persistent or transient blockade of the angiotensin II (ANG II) receptor AT(1) on the development of hypertension and end-organ damage in hypertensive Ren-2 transgenic rats (TGR), and second to assess the potential role of AT(2) receptors in the control of blood pressure (BP) in this monogenetic model of hypertension. Male heterozygous TGR and Hannover Sprague-Dawley (HanSD) rats fed a normal salt diet were treated from day 32 of age either persistently until the end of the experiment (day 100 of age) or transiently until day 56 of age with the selective AT(1) receptor antagonist candesartan or with the combination of candesartan and the AT(2) receptor antagonist PD 123319. Persistent treatment with candesartan completely prevented the rise in BP, proteinuria and the increase in left ventricular weight/body weight ratio, whereas transient treatment with candesartan was effective only as long as the drug was administered. In the presence of candesartan, PD 123319 was without effect. Our results show that in male heterozygous TGR persistent candesartan treatment completely prevented hypertension and end-organ damage as long as the drug was administered, whereas transient AT(1 )receptor blockade had no long-term effects. Copyright 2007 S. Karger AG, Basel.
Keywords: blokátory receptorů AT1 pro angiotensin II; financování organizované; Animals; Benzimidazoles; Kidney; Proteinuria; Hypertension, Renal; receptor angiotensinu typ 2; Animals, Genetically Modified; Receptor, Angiotensin, Type 1; renální hypertenze; receptor angiotensinu typ 1; benzimidazoly; Renin; Receptor, Angiotensin, Type 2; Tetrazoles; tetrazoly; krevní tlak; Rats, Sprague-Dawley; Financing, Organized; Male; potkani Sprague-Dawley; krysa rodu Rattus; zvířata; mužské pohlaví; Angiotensin II Type 1 Receptor Blockers; geneticky modifikovaná zvířata; ledviny; Blood Pressure; renin; Rats; proteinurie